Liberté, éducation et pouvoir. Lecture non-directive à partir des travaux de Daniel Hameline - Émilie Osmont (Recherches en Éducation)
The Renaissance humanism ordered education for freedom and, typically, philosphy usually links the concept of freedom with the idea of political community, whose power is one of the attributes. But when we want to think the relation between freedom, education and power in pedagogic terms, we come up against requirements of praxis: it is not enough to think, it is also about to do. Concretely. Then to tell it. About that, Daniel Hameline’s non-directive experience and books written with Marie-Joëlle Dardelin, are an example at a specific time crossing as much by social protest movements, including about School, as theories on relations of power in the French education system. This paper first describes non-directive teaching function comparing with the traditional function, in order to highlight the asymmetry of a relationship experiencing an institutional order. Although this was not his intent, non-directivity is then presented as a challenge to the political order established by focusing on the conditions of creation to the detriment of what is already existing. But the valuation of the actor has limits, the very ones who make the school game, and the emancipation of child can not be though without his subjugation. Between liberalization and ending school system, Daniel Hameline choose the "middle way" with critical education.